Tingkat Profitabilitas Bank Syariah Indonesia (BSI) Pasca Merger - Sri Andriani (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2023)
Bank Syariah Indonesia (BSI) is a government-owned Islamic bank that is the result of the merger and acquisition of Bank Mandiri Syariah, Bank BRI Syariah, and Bank BNI Syariah. Despite the COVID-19 pandemic, BSI's performance continues to show a positive trend. This research aims to determine the performance of BSI, especially the ability to generate profits (profit), by considering the conditions of NPF, BOPO, and FDR. As an associative research using multiple linear regression data analysis. The data used is quarterly data starting from 2020–2023 (Q1). The results of this research show that NPF has a negative but not significant effect on ROA, and BOPO has a negative and significant effect on ROA. While FDR has a positive but not significant effect on ROA.